Rancang Bangun Sistem Monitoring Kinerja Fresh Water Generator Menggunakan Arduino Mega 2560 - Bayu Rahmiyarto Ar-Ridho; Edi Kurniawan; Romanda Annas Amrullah (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
Fresh water is a basic need of the ship's crew in supporting the creation of smooth ship operating activities, therefore it is also necessary to have an auxiliary aircraft that can produce its own fresh water on board to reduce ship operating costs, which is called the Fresh Water Generator (FWG). FWG is an auxiliary aircraft that can convert seawater into fresh water by evaporation and condensation processes. Therefore, it is necessary to have a tool to monitor the performance of the fresh water generator. The purpose of this research is none other than to monitor temperature conditions, water TDS, and conditions on the input and output streams of the fresh water generator evaporator filter to be more optimal and efficient and to determine the reliability of the fresh water generator performance equipment system using a long distance in order to create better and higher quality fresh water production on board. This research uses a prototyping method system. After designing and testing the tool monitoring system for the performance of fresh water generators using Arduino mega 2560 based on LoRa Ra-02, this system is one of the new technologies that can monitor the performance of fresh water generators to be more efficient and reliable. Then the readings of all sensors can work properly with an average percentage error on the Max 6675 temperature sensor of 0.58%, pressure transmiter sensor 1 of 2.04%, pressure transmiter sensor 2 of 2.04%, and TDS sensor of 1,70% and the distance to communication between the receiver and transceiver reaches a range of 200 meters without obstacles and 97 meters through obstacles around.